Structural properties of nonionic Tween80 micelle in water elucidated by molecular dynamics simulation. - Karjiban, Roghayeh Abedi; Basri, Mahiran; Abdul Rahman, Mohd Basyaruddin; Salleh, Abu Bakar (2012)
Chemical penetration enhancers such as micelles can be formed from the solubilisation of the nonionic surfactants in the nanoemulsion system which may then provide an effective solution to the problems associated with drug delivery systems. The structural properties of micelles comprising 5, 20, and 30 molecules of the nonionic surfactant Tween80 were investigated by all-atom level molecular dynamics simulation in explicit water system. The micelles with higher aggregation numbers showed a prolate shape, with the surface being dominated by the polar hydrophilic moieties of surfactant molecules. The average radius of gyration was between 1.1-4.9 nm while the effective radius, determined from the radius of gyration was between 1.4-3.2 nm. The estimated structural properties of the micelles formed may give us a more detail insight in understanding the complexity of these classes of nonionic surfactants.